O novo ensino médio na rede pública estadual de ensino de Minas Gerais: um estudo da implementação do tempo integral e integrado - Heyde Ferreira Gomes (2019)
The aim of this research was to investigate the implementation of the public policy O Novo Ensino Médio [New High School] in the Public School of Minas Gerais after the approval of the Law 13.415 in February 16, 2017, in order to understand and analyze how full-time school influences the teaching-learning processes and the teaching practices. This study is justified by the fact that High School is considered a stage of Basic Education that presents high rates of failure, dropout and low performance of students in assessment (BRASIL, 2016c). To approach this scenario, it was considered relevant to carry out a literature review from the 1990s, exploring the contributions of researchers such as Dayrell (2007), Gomes (2005, 2014 and 2017), Krawczyk (2011), Ferreira (2017) and Leão (2018). Documentary and field research was also carried out, with a qualitative approach, linked to the socio-historical assumptions of Vygotsky (1930/2001). The data were analyzed through the content analysis, based on the contributions of Bardin (2010) in order to understand the main implications of the implementation of this educational public policy. The main outcomes observed in this research revealed that the major demands for the improvement of High school in full-time were a) investments in continuing teacher education; b) an offering of an effective project for Integral and Integrated Education; c) Improvement in the use of space and time in pedagogical activities; d) diversification of the pedagogical resources, and e) an improved dialogue with the demands of young people. Thereby, it was concluded that the implementation of full-time in the school was simply an increasing of the school time, without promoting any effective Integral Education, causing the young students to attend a high school with an extensive workload, however pedagogically and structurally poor.